Growth evaluation of native tree species planted on post coal mining reclamation site in East Kalimantan, Indonesia - DEWI AYU LESTARI; ABBAN PUTRI FIQA; FAUZIAH FAUZIAH; SUGENG BUDIHARTA (Society for Indonesian Biodiversity, 2019)
Lestari DA, Fiqa AP, Fauziah, Budiharta S. 2019. Growth evaluation of native tree species planted on post coal mining reclamation site in East Kalimantan, Indonesia. Biodiversitas 20: 134-143. Mining activities affect environmental qualities including the loss of vegetation cover and the damages of physical, chemical and biological properties of soil. As such, regulations enacted by the Indonesian Government state a legal obligation for mining companies to carry out reclamation on post coal mining site. Reclamation is an activity carried out to organize, restore and improve of environmental quality after mining operations to enhance the highly disturbed ecosystem of mined land into ecologically usable state. Yet, there is little body of knowledge on how to monitor the effectiveness of reclamation in improving environmental quality of ex-mining land. Aims of this study are to evaluate of the growth of native tree species planted on various types of reclamation sites in a mining concession in East Kalimantan, and to analyze the most influencing factor of their growth. Growth parameters measured in this research were plant height, stem diameter and branch-free stem height of the planted species. Micro-climatic factors and diversity of understorey plants were also measured as environmental parameters. PCA (Principal Component Analysis) analysis was conducted using PAST 4.0. statistical program. The results shows that reclamation area of post coal mining in the study site which is most suitable for local plant species, especially Shorea balangeran, has a sloping terrain. PCA shows that factor having maximum influence on growth of planted species on the reclamation site is pH of soil. The higher is the soil pH (i.e. less acid), the better is the species growth because the soil conditions in the post-coal mining area tend to be acidic. This research suggests that in post coal mining reclamation using native trees two key factors to enhance growth performance of planted species are sloping terrain so as water is not inundated and soil pH so as it is not too acid.